A double metal sulfate composite catalyst and its preparation method and application
By doping the sulfates of BaSO4 and other metals in the catalyst, a bimetallic sulfate composite catalyst is formed, which solves the problem of carbon deposits and inactivation of existing catalysts during the thermal cracking of HCFC-142b, and achieves a catalytic effect of high selectivity, stability and low reaction temperature.
Patent Information
- Application Number
- CN202111159267.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-30
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-09-30
AI Technical Summary
The existing catalysts are prone to carbon deposits and inactivated during the thermal cracking of HCFC-142b, and have poor selectivity and stability, making it difficult to effectively reduce the reaction temperature and improve the catalytic conversion rate.
A bimetal sulfate composite catalyst is used to form a solid solution by doping BaSO4 and sulfates of metals such as Pb, Ag, Y, Sr, Ca, Ni, etc. to improve the activity, selectivity and stability of the catalyst.
The anti-chlorination effect of the catalyst is achieved, the catalytic conversion rate and selectivity is improved, the reaction temperature is reduced, the service life of the catalyst is extended, and the cost is reduced.
Smart Images

Figure BDA0003289485160000061 
Figure BDA0003289485160000071 
Figure BDA0003289485160000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of multiphase thermal catalysts, and in particular relates to a bimetallic sulfate composite catalyst and a preparation method and application thereof. Background Art
[0002] 1,1-Difluoro-1-chloroethane (HCFC-142b) is a hydrochlorofluorocarbon (HCFCs) with the chemical formula CF2ClCH3. It is the main industrial raw material for the production of polyvinylidene fluoride (PVDF) monomer vinylidene fluoride (VDF). Since the early 1990s, the content of HCFC-142b in the atmosphere has been steadily increasing. Its high greenhouse effect potential will pollute the atmospheric environment. Currently, HCFC-142b can be used as a raw material to produce polyvinylidene fluoride to achieve its resource conversion.
[0003] The temperature of thermal cracking of HCFC-142b is generally between 600 and 800°C, which can easily lead to carbon deposition, coking, side reactions and disproportionation reactions, thus affecting the yield of the target product VDF. Adding a catalyst can reduce the reaction energy barrier of HCFC-142b dehydrochlorination and greatly reduce the temperature required for the reaction. It is an effective and environmentally friendly way to produce VDF. At present, there are various disadvantages in the catalysts for catalytic cracking of HCFC-142b to remove HCl, such as activated carbon catalysts are easy to deactivate and difficult to regenerate; metal oxides are easy to react with hydrogen chloride and deactivate quickly; metal fluorides prefer to remove HF, reducing the selectivity of the reaction; and although metal chlorides do not react with hydrogen chloride, they have poor activity, etc. Therefore, it is of great significance to develop a highly selective catalyst that is resistant to chlorination in the reaction.
[0004] For the gas phase dehydrochlorination of chlorofluorocarbons (HCFCs) to produce fluorinated olefins (HFOs), the affinity of the main catalyst metal to the Cl element has an important influence on the reaction selectivity and conversion activity. BaSO4 has a strong affinity for Cl or a strong selective adsorption of Cl, so it has a high selective catalytic activity for the main product vinylidene fluoride (VDF), but its stability is relatively poor. By doping other metals with high activity and stability, a solid solution can be formed, and the interaction between metals can be strengthened, thereby achieving the purpose of having both high activity and high selectivity, which has good application prospects in the field of selective dehydrochlorination. Summary of the invention
[0005] In view of the above technical problems existing in the prior art, the purpose of the present invention is to provide a bimetallic sulfate composite catalyst and its preparation method and application. The catalyst of the present invention has the advantages of short preparation cycle, high catalytic yield and simple preparation method. The application of the composite catalyst of the present invention in the preparation of vinylidene fluoride by catalytic cracking and dehydrochlorination of 1,1-difluoro-1-chloroethane has the advantages of low reaction temperature, high catalytic conversion rate, high catalytic selectivity, good catalytic stability and low catalyst cost.
[0006] The bimetallic sulfate composite catalyst is characterized in that the composite catalyst uses BaSO4 as a main catalyst and a sulfate of any one of Pb, Ag, Y, Sr, Ca, and Ni as a co-catalyst.
[0007] The method for preparing the bimetallic sulfate composite catalyst is characterized in that it is prepared by a coprecipitation method, comprising the following steps:
[0008] 1) Dissolve the barium source and the co-catalyst precursor in deionized water, stir for 20 to 40 minutes, then drop the aqueous solution of the precipitant into the solution, stir and react for 2 to 4 hours to obtain a precipitated mixture;
[0009] 2) The precipitated mixture obtained in step 1) is aged at room temperature, then filtered, washed with water, and dried to obtain a bimetallic sulfate composite catalyst.
[0010] The method for preparing a bimetallic sulfate composite catalyst is characterized in that the barium source in step 1) is one of barium nitrate, barium chloride or barium hydroxide, preferably barium nitrate.
[0011] The preparation method of the bimetallic sulfate composite catalyst is characterized in that in step 1), the co-catalyst precursor is one of the nitrates, chlorides or hydroxides of any one of the metals Pb, Ag, Y, Sr, Ca and Ni, preferably the nitrates of any one of the metals Pb, Ag, Y, Sr, Ca and Ni, and more preferably the nitrates of any one of the metals Y, Sr, Ca and Ni.
[0012] The method for preparing a bimetallic sulfate composite catalyst is characterized in that in step 1), the molar ratio of the metal element in the promoter precursor to the barium element in the barium source is 0.01 to 2:1, preferably 0.1 to 1:1.
[0013] The method for preparing a bimetallic sulfate composite catalyst is characterized in that in step 1), the stirring reaction temperature is 10 to 70°C, preferably 30 to 50°C.
[0014] The method for preparing a bimetallic sulfate composite catalyst is characterized in that in step 1), the precipitant is one of ammonium sulfate, ammonium bisulfate or dilute sulfuric acid, and the molar ratio of the precipitant to the barium element in the barium source is 1 to 2:1, preferably 1.1 to 1.5:1.
[0015] The method for preparing a bimetallic sulfate composite catalyst is characterized in that in step 2), the aging time is 0.2 to 3 hours, preferably 0.5 to 1.5 hours; the drying temperature is 60 to 140°C, the drying time is 8 to 16 hours, preferably the drying temperature is 90 to 110°C, and the drying time is preferably 11 to 13 hours.
[0016] The bimetallic sulfate composite catalyst is used in the reaction of catalyzing the gas phase dehydrochlorination of fluorine-containing chloroalkanes to prepare fluorine-containing olefins.
[0017] Furthermore, the fluorine-containing chloroalkane is 1,1-difluoro-1-chloroethane, and the fluorine-containing olefin is vinylidene fluoride; the process of using the bimetallic sulfate composite catalyst in catalyzing the gas-phase dehydrochlorination of fluorine-containing chloroalkane to prepare fluorine-containing olefin is: the catalyst is loaded into a fixed bed reactor, and a mixed gas of N2 and fluorine-containing chloroalkane is introduced, the feed volume ratio of N2 and fluorine-containing chloroalkane is 1:0.5-2, and the total space velocity of the mixed gas of N2 and fluorine-containing chloroalkane is 250-300h -1 , the reaction temperature is 350-450°C, and the reaction produces vinylidene fluoride product.
[0018] By adopting the above technology, compared with the prior art, the beneficial effects of the present invention are as follows:
[0019] The bimetallic sulfate composite catalyst of the present invention is obtained by adding a co-catalyst, such as a sulfate of any one of Y, Sr, Ca and Ni as a co-catalyst, and the high conversion rate of Ba salt is combined with the high selectivity and anti-chlorination effect of M metal salt, so that the catalyst has anti-chlorination effect, solves the problems of carbon deposition and deactivation of activated carbon, metal oxide and metal fluoride catalysts, and improves the activity, selectivity and stability of the bimetallic sulfate composite catalyst. The obtained bimetallic sulfate composite catalyst is used for catalytic cracking and de-HCl removal of 1,1-difluoro-1-chloroethane to prepare vinylidene fluoride, and it is found that the catalyst has the advantages of low reaction temperature, good catalytic stability, high selectivity and the like. DETAILED DESCRIPTION
[0020] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0021] Example 1
[0022] 0.040 mol Ba(NO3)2 and 0.040 mol Pb(NO3)2 were dissolved in 200 mL deionized water at 50°C, stirred in a water bath for 40 min, and then 200 mL 0.600 mol / L (NH4)2SO4 aqueous solution was added dropwise. The mixture was stirred at 50°C for 4 h, and then aged at room temperature for 1.5 h. After that, the mixture was filtered and washed with water three times, and dried in an oven at 110°C for 11 h to obtain a catalyst sample. After tabletting, it was sieved with a 20-40 mesh sieve.
[0023] The bimetallic sulfate composite catalyst prepared above is used to catalyze the cracking of 1,1-difluoro-1-chloroethane (HCFC-142b) to prepare 1,1-difluoroethylene (VDF), and the reaction formula is as follows:
[0024] CF2ClCH3→CF2=CH2+HCl
[0025] The reaction conditions are as follows: the catalyst is loaded into the fixed bed reactor, the catalyst loading amount is 2 mL, a mixed gas of N2 and HCFC-142b is introduced, the N2 flow rate is 5 mL / min, the HCFC-142b flow rate is 5 mL / min, and the total space velocity of the mixed gas of N2 and HCFC-142b is 300 h -1 The reaction temperature was 400°C. Samples were taken and analyzed after 30 hours of reaction. The evaluation results are shown in Table 1.
[0026] Example 2
[0027] 0.040 mol Ba(NO3)2 and 0.020 mol Pb(NO3)2 were dissolved in 150 mL deionized water at 40°C, stirred in a water bath for 30 min, and then 150 mL 0.520 mol / L NH4HSO4 aqueous solution was added dropwise. The mixture was stirred at 40°C for 3 h, then aged at room temperature for 1 h. After that, the mixture was filtered and washed with water 3 times, and dried in an oven at 100°C for 12 h to obtain a catalyst sample. After tabletting, it was sieved with a 20-40 mesh sieve.
[0028] The bimetallic sulfate composite catalyst prepared above was used to catalyze the cracking of 1,1-difluoro-1-chloroethane (HCFC-142b) to prepare 1,1-difluoroethylene (VDF). The reaction conditions were as follows: the catalyst was loaded into a fixed bed reactor with a catalyst loading of 2 mL, a mixed gas of N2 and HCFC-142b was introduced, the N2 flow rate was 5 mL / min, the HCFC-142b flow rate was 5 mL / min, and the total space velocity of the mixed gas of N2 and HCFC-142b was 300 h / min. -1 The reaction temperature was 400°C. Samples were taken and analyzed after 30 hours of reaction. The evaluation results are shown in Table 1.
[0029] Example 3
[0030] 0.040 mol Ba(NO3)2 and 0.004 mol Pb(NO3)2 were dissolved in 110 mL deionized water at 30°C, stirred in a water bath for 20 min, and then 110 mL 0.440 mol / L dilute H2SO4 aqueous solution was added dropwise. The mixture was stirred at 30°C for 2 h, then aged at room temperature for 0.5 h. After that, the mixture was filtered and washed with water three times, and dried in an oven at 90°C for 13 h to obtain a catalyst sample. After tabletting, it was sieved with a 20-40 mesh sieve.
[0031] The bimetallic sulfate composite catalyst prepared above was used to catalyze the cracking of 1,1-difluoro-1-chloroethane (HCFC-142b) to prepare 1,1-difluoroethylene (VDF). The reaction conditions were as follows: the catalyst was loaded into a fixed bed reactor with a catalyst loading of 2 mL, a mixed gas of N2 and HCFC-142b was introduced, the N2 flow rate was 5 mL / min, the HCFC-142b flow rate was 5 mL / min, and the total space velocity of the mixed gas of N2 and HCFC-142b was 300 h / min. -1 The reaction temperature was 400°C. Samples were taken and analyzed after 30 hours of reaction. The evaluation results are shown in Table 1.
[0032] Table 1: Conversion rate of HCFC-142b and selectivity of VDF over catalysts with different Pb contents
[0033]
[0034] Example 4
[0035] 0.040 mol Ba(NO3)2 and 0.040 mol AgNO3 were dissolved in 200 mL deionized water at 50°C, stirred in a water bath for 40 min, and then 150 mL 0.600 mol / L (NH4)2SO4 aqueous solution was added dropwise. The mixture was stirred at 50°C for 4 h, and then aged at room temperature for 1.5 h. After that, the mixture was filtered and washed with water three times, and dried in an oven at 110°C for 11 h to obtain a catalyst sample. After tabletting, it was sieved with a 20-40 mesh sieve.
[0036] The bimetallic sulfate composite catalyst prepared above was used to catalyze the cracking of 1,1-difluoro-1-chloroethane (HCFC-142b) to prepare 1,1-difluoroethylene (VDF). The reaction conditions were as follows: the catalyst was loaded into a fixed bed reactor with a catalyst loading of 2 mL, a mixed gas of N2 and HCFC-142b was introduced, the N2 flow rate was 5 mL / min, the HCFC-142b flow rate was 5 mL / min, and the total space velocity of the mixed gas of N2 and HCFC-142b was 300 h / min. -1 The reaction temperature was 400°C. Samples were taken and analyzed after 30 hours of reaction. The evaluation results are shown in Table 2.
[0037] Example 5
[0038] 0.040 mol Ba(NO3)2 and 0.020 mol AgNO3 were dissolved in 150 mL deionized water at 40°C, stirred in a water bath for 30 min, and then 125 mL 0.520 mol / L NH4HSO4 aqueous solution was added dropwise. The mixture was stirred at 40°C for 3 h, then aged at room temperature for 1 h. After that, the mixture was filtered and washed with water 3 times, and dried in an oven at 100°C for 12 h to obtain a catalyst sample. After tabletting, it was sieved with a 20-40 mesh sieve.
[0039] The bimetallic sulfate composite catalyst prepared above was used to catalyze the cracking of 1,1-difluoro-1-chloroethane (HCFC-142b) to prepare 1,1-difluoroethylene (VDF). The reaction conditions were as follows: the catalyst was loaded into a fixed bed reactor with a catalyst loading of 2 mL, a mixed gas of N2 and HCFC-142b was introduced, the N2 flow rate was 5 mL / min, the HCFC-142b flow rate was 5 mL / min, and the total space velocity of the mixed gas of N2 and HCFC-142b was 300 h / min. -1 The reaction temperature was 400°C. Samples were taken and analyzed after 30 hours of reaction. The evaluation results are shown in Table 2.
[0040] Example 6
[0041] 0.040 mol Ba(NO3)2 and 0.004 mol AgNO3 were dissolved in 110 mL deionized water at 30°C, stirred in a water bath for 20 min, and then 105 mL 0.440 mol / L dilute H2SO4 aqueous solution was added dropwise. The mixture was stirred at 30°C for 2 h, and then aged at room temperature for 0.5 h. After that, the mixture was filtered and washed with water three times, and dried in an oven at 90°C for 13 h to obtain a catalyst sample. After tabletting, it was sieved with a 20-40 mesh sieve.
[0042] The bimetallic sulfate composite catalyst prepared above was used to catalyze the cracking of 1,1-difluoro-1-chloroethane (HCFC-142b) to prepare 1,1-difluoroethylene (VDF). The reaction conditions were as follows: the catalyst was loaded into a fixed bed reactor with a catalyst loading of 2 mL, a mixed gas of N2 and HCFC-142b was introduced, the N2 flow rate was 5 mL / min, the HCFC-142b flow rate was 5 mL / min, and the total space velocity of the mixed gas of N2 and HCFC-142b was 300 h / min. -1 The reaction temperature was 400°C. Samples were taken and analyzed after 30 hours of reaction. The evaluation results are shown in Table 2.
[0043] Table 2: Conversion rate of HCFC-142b and selectivity of VDF over catalysts with different Ag contents
[0044]
[0045] It can be seen from the experimental results of Examples 1 to 6 that: when the reaction was continuously evaluated for 30 hours using Ba-Pb bimetallic sulfate or Ba-Ag bimetallic sulfate as a catalyst, although the conversion rate of the catalytic reaction was average, the catalytic selectivity was very high, reaching more than 96%, and a good reaction effect was achieved.
[0046] Example 7
[0047] 0.040 mol Ba(NO3)2 and 0.040 mol Y(NO3)3·6H2O were dissolved in 200 mL deionized water at 50°C, stirred in a water bath for 40 min, and then 250 mL 0.600 mol / L (NH4)2SO4 aqueous solution was added dropwise. The mixture was stirred at 50°C for 4 h, then aged at room temperature for 1.5 h, filtered, washed with water 3 times, and dried in an oven at 110°C for 11 h to obtain a catalyst sample. After tabletting, it was sieved with a 20-40 mesh sieve.
[0048] The bimetallic sulfate composite catalyst prepared above was used to catalyze the cracking of 1,1-difluoro-1-chloroethane (HCFC-142b) to prepare 1,1-difluoroethylene (VDF). The reaction conditions were as follows: the catalyst was loaded into a fixed bed reactor with a catalyst loading of 2 mL, a mixed gas of N2 and HCFC-142b was introduced, the N2 flow rate was 5 mL / min, the HCFC-142b flow rate was 5 mL / min, and the total space velocity of the mixed gas of N2 and HCFC-142b was 300 h / min. -1 The reaction temperature was 400°C. Samples were taken and analyzed after 30 hours of reaction. The evaluation results are shown in Table 3.
[0049] Example 8
[0050] 0.040 mol BaCl2·2H2O and 0.020 mol YCl3·6H2O were dissolved in 150 mL deionized water at 40°C, stirred in a water bath for 30 min, and then 175 mL 0.520 mol / L NH4HSO4 aqueous solution was added dropwise. The mixture was stirred at 40°C for 3 h, then aged at room temperature for 1 h. After that, the mixture was filtered and washed with water three times, and dried in an oven at 100°C for 12 h to obtain a catalyst sample. After tabletting, the sample was sieved with a 20-40 mesh sieve.
[0051] The bimetallic sulfate composite catalyst prepared above was used to catalyze the cracking of 1,1-difluoro-1-chloroethane (HCFC-142b) to prepare 1,1-difluoroethylene (VDF). The reaction conditions were as follows: the catalyst was loaded into a fixed bed reactor with a catalyst loading of 2 mL, a mixed gas of N2 and HCFC-142b was introduced, the N2 flow rate was 5 mL / min, the HCFC-142b flow rate was 5 mL / min, and the total space velocity of the mixed gas of N2 and HCFC-142b was 300 h / min. -1 The reaction temperature was 400°C. Samples were taken and analyzed after 30 hours of reaction. The evaluation results are shown in Table 3.
[0052] Example 9
[0053] 0.040 mol Ba(NO3)2 and 0.004 mol Y(NO3)3·6H2O were dissolved in 110 mL deionized water at 30°C, stirred in a water bath for 20 min, and then 115 mL 0.440 mol / L dilute H2SO4 aqueous solution was added dropwise. The mixture was stirred at 30°C for 2 h, then aged at room temperature for 0.5 h. After that, the mixture was filtered, washed with water three times, and dried in an oven at 90°C for 13 h to obtain a catalyst sample. After tabletting, it was sieved with a 20-40 mesh sieve.
[0054] The bimetallic sulfate composite catalyst prepared above was used to catalyze the cracking of 1,1-difluoro-1-chloroethane (HCFC-142b) to prepare 1,1-difluoroethylene (VDF). The reaction conditions were as follows: the catalyst was loaded into a fixed bed reactor with a catalyst loading of 2 mL, a mixed gas of N2 and HCFC-142b was introduced, the N2 flow rate was 5 mL / min, the HCFC-142b flow rate was 5 mL / min, and the total space velocity of the mixed gas of N2 and HCFC-142b was 300 h / min. -1 The reaction temperature was 400°C. Samples were taken and analyzed after 30 hours of reaction. The evaluation results are shown in Table 3.
[0055] Table 3: Conversion rate of HCFC-142b and selectivity of VDF for catalysts with different Y contents
[0056]
[0057] Example 10
[0058] 0.040 mol Ba(NO3)2 and 0.040 mol Sr(NO3)2 were dissolved in 200 mL deionized water at 50°C, stirred in a water bath for 40 min, and then 200 mL 0.600 mol / L (NH4)2SO4 aqueous solution was added dropwise. The mixture was stirred at 50°C for 4 h, and then aged at room temperature for 1.5 h. After that, the mixture was filtered and washed with water three times, and dried in an oven at 110°C for 11 h to obtain a catalyst sample. After tabletting, it was sieved with a 20-40 mesh sieve.
[0059] The bimetallic sulfate composite catalyst prepared above was used to catalyze the cracking of 1,1-difluoro-1-chloroethane (HCFC-142b) to prepare 1,1-difluoroethylene (VDF). The reaction conditions were as follows: the catalyst was loaded into a fixed bed reactor with a catalyst loading of 2 mL, a mixed gas of N2 and HCFC-142b was introduced, the N2 flow rate was 5 mL / min, the HCFC-142b flow rate was 5 mL / min, and the total space velocity of the mixed gas of N2 and HCFC-142b was 300 h / min. -1 The reaction temperature was 400°C. Samples were taken and analyzed after 30 hours of reaction. The evaluation results are shown in Table 4.
[0060] Embodiment 11
[0061] 0.040 mol BaCl2·2H2O and 0.020 mol SrCl2·6H2O were dissolved in 150 mL deionized water at 40°C, stirred in a water bath for 30 min, and then 150 mL 0.520 mol / L NH4HSO4 aqueous solution was added dropwise. The mixture was stirred at 40°C for 3 h, then aged at room temperature for 1 h. After that, the mixture was filtered and washed with water three times, and dried in an oven at 100°C for 12 h to obtain a catalyst sample. After tabletting, the sample was sieved with a 20-40 mesh sieve.
[0062] The bimetallic sulfate composite catalyst prepared above was used to catalyze the cracking of 1,1-difluoro-1-chloroethane (HCFC-142b) to prepare 1,1-difluoroethylene (VDF). The reaction conditions were as follows: the catalyst was loaded into a fixed bed reactor with a catalyst loading of 2 mL, a mixed gas of N2 and HCFC-142b was introduced, the N2 flow rate was 5 mL / min, the HCFC-142b flow rate was 5 mL / min, and the total space velocity of the mixed gas of N2 and HCFC-142b was 300 h / min. -1 The reaction temperature was 400°C. Samples were taken and analyzed after 30 hours of reaction. The evaluation results are shown in Table 4.
[0063] Example 12
[0064] 0.040 mol Ba(OH)2·8H2O and 0.004 mol Sr(OH)2 were dissolved in 110 mL deionized water at 30°C, stirred in a water bath for 20 min, and then 110 mL 0.440 mol / L dilute H2SO4 aqueous solution was added dropwise. The mixture was stirred at 30°C for 2 h, then aged at room temperature for 0.5 h. After that, the mixture was filtered and washed with water three times, and dried in an oven at 90°C for 13 h to obtain a catalyst sample. After tabletting, it was sieved with a 20-40 mesh sieve.
[0065] The bimetallic sulfate composite catalyst prepared above was used to catalyze the cracking of 1,1-difluoro-1-chloroethane (HCFC-142b) to prepare 1,1-difluoroethylene (VDF). The reaction conditions were as follows: the catalyst was loaded into a fixed bed reactor with a catalyst loading of 2 mL, a mixed gas of N2 and HCFC-142b was introduced, the N2 flow rate was 5 mL / min, the HCFC-142b flow rate was 5 mL / min, and the total space velocity of the mixed gas of N2 and HCFC-142b was 300 h / min. -1 The reaction temperature was 400°C. Samples were taken and analyzed after 30 hours of reaction. The evaluation results are shown in Table 4.
[0066] Table 4: Conversion rate of HCFC-142b and selectivity of VDF for catalysts with different Sr contents
[0067]
[0068] Example 13
[0069] 0.040 mol Ba(NO3)2 and 0.040 mol Ca(NO3)2·4H2O were dissolved in 200 mL deionized water at 50°C, stirred in a water bath for 40 min, and then 200 mL 0.600 mol / L (NH4)2SO4 aqueous solution was added dropwise. The mixture was stirred at 50°C for 4 h, then aged at room temperature for 1.5 h. After that, the mixture was filtered and washed with water three times, and dried in an oven at 110°C for 11 h to obtain a catalyst sample. After tabletting, it was sieved with a 20-40 mesh sieve.
[0070] The bimetallic sulfate composite catalyst prepared above was used to catalyze the cracking of 1,1-difluoro-1-chloroethane (HCFC-142b) to prepare 1,1-difluoroethylene (VDF). The reaction conditions were as follows: the catalyst was loaded into a fixed bed reactor with a catalyst loading of 2 mL, a mixed gas of N2 and HCFC-142b was introduced, the N2 flow rate was 5 mL / min, the HCFC-142b flow rate was 5 mL / min, and the total space velocity of the mixed gas of N2 and HCFC-142b was 300 h / min. -1 The reaction temperature was 400°C. Samples were taken and analyzed after 30 hours of reaction. The evaluation results are shown in Table 5.
[0071] Embodiment 14
[0072] 0.040 mol BaCl2·2H2O and 0.020 mol CaCl2 were dissolved in 150 mL deionized water at 40°C, stirred in a water bath for 30 min, and then 150 mL 0.520 mol / L NH4HSO4 aqueous solution was added dropwise. The mixture was stirred at 40°C for 3 h, then aged at room temperature for 1 h. After that, the mixture was filtered and washed with water three times, and dried in an oven at 100°C for 12 h to obtain a catalyst sample. After tabletting, the sample was sieved with a 20-40 mesh sieve.
[0073] The bimetallic sulfate composite catalyst prepared above was used to catalyze the cracking of 1,1-difluoro-1-chloroethane (HCFC-142b) to prepare 1,1-difluoroethylene (VDF). The reaction conditions were as follows: the catalyst was loaded into a fixed bed reactor with a catalyst loading of 2 mL, a mixed gas of N2 and HCFC-142b was introduced, the N2 flow rate was 5 mL / min, the HCFC-142b flow rate was 5 mL / min, and the total space velocity of the mixed gas of N2 and HCFC-142b was 300 h / min. -1 The reaction temperature was 400°C. Samples were taken and analyzed after 30 hours of reaction. The evaluation results are shown in Table 5.
[0074] Embodiment 15
[0075] Dissolve 0.040 mol Ba(NO3)2 and 0.004 mol Ca(NO3)2 in 110 mL deionized water at 30°C, stir in a water bath for 20 min, then dropwise add 110 mL 0.440 mol / L dilute H2SO4 aqueous solution, stir and react at 30°C for 2 h, then age at room temperature for 0.5 h, filter and wash with water three times, then dry in an oven at 90°C for 13 h to obtain a catalyst sample, press into tablets and sieve with a 20-40 mesh sieve.
[0076] The bimetallic sulfate composite catalyst prepared above was used to catalyze the cracking of 1,1-difluoro-1-chloroethane (HCFC-142b) to prepare 1,1-difluoroethylene (VDF). The reaction conditions were as follows: the catalyst was loaded into a fixed bed reactor with a catalyst loading of 2 mL, a mixed gas of N2 and HCFC-142b was introduced, the N2 flow rate was 5 mL / min, the HCFC-142b flow rate was 5 mL / min, and the total space velocity of the mixed gas of N2 and HCFC-142b was 300 h / min. -1 The reaction temperature was 400°C. Samples were taken and analyzed after 30 hours of reaction. The evaluation results are shown in Table 5.
[0077] Table 5: Conversion rate of HCFC-142b and selectivity of VDF for catalysts with different Ca contents
[0078]
[0079] Example 16
[0080] 0.040 mol BaCl2 and 0.040 mol Ni(NO3)2·6H2O were dissolved in 200 mL deionized water at 50°C, stirred in a water bath for 40 min, and then 200 mL 0.600 mol / L (NH4)2SO4 aqueous solution was added dropwise. The mixture was stirred at 50°C for 4 h, then aged at room temperature for 1.5 h, filtered, washed with water 3 times, and dried in an oven at 110°C for 11 h to obtain a catalyst sample. After tabletting, the sample was sieved with a 20-40 mesh sieve.
[0081] The bimetallic sulfate composite catalyst prepared above was used to catalyze the cracking of 1,1-difluoro-1-chloroethane (HCFC-142b) to prepare 1,1-difluoroethylene (VDF). The reaction conditions were as follows: the catalyst was loaded into a fixed bed reactor with a catalyst loading of 2 mL, a mixed gas of N2 and HCFC-142b was introduced, the N2 flow rate was 5 mL / min, the HCFC-142b flow rate was 5 mL / min, and the total space velocity of the mixed gas of N2 and HCFC-142b was 300 h / min. -1 The reaction temperature was 400°C. After 30 hours of reaction, samples were taken for analysis. The evaluation results are shown in Table 6.
[0082] Embodiment 17
[0083] 0.040 mol BaCl2·2H2O and 0.020 mol NiCl2·6H2O were dissolved in 150 mL deionized water at 40°C, stirred in a water bath for 30 min, and then 150 mL 0.520 mol / L NH4HSO4 aqueous solution was added dropwise. The mixture was stirred at 40°C for 3 h, then aged at room temperature for 1 h. After that, the mixture was filtered and washed with water three times, and dried in an oven at 100°C for 12 h to obtain a catalyst sample. After tabletting, the sample was sieved with a 20-40 mesh sieve.
[0084] The bimetallic sulfate composite catalyst prepared above was used to catalyze the cracking of 1,1-difluoro-1-chloroethane (HCFC-142b) to prepare 1,1-difluoroethylene (VDF). The reaction conditions were as follows: the catalyst was loaded into a fixed bed reactor with a catalyst loading of 2 mL, a mixed gas of N2 and HCFC-142b was introduced, the N2 flow rate was 5 mL / min, the HCFC-142b flow rate was 5 mL / min, and the total space velocity of the mixed gas of N2 and HCFC-142b was 300 h / min. -1 The reaction temperature was 400°C. After 30 hours of reaction, samples were taken for analysis. The evaluation results are shown in Table 6.
[0085] Embodiment 18
[0086] 0.040 mol BaCl2 and 0.004 mol Ni(NO3)2·6H2O were dissolved in 110 mL deionized water at 30°C, stirred in a water bath for 20 min, and then 110 mL 0.440 mol / L dilute H2SO4 aqueous solution was added dropwise. The mixture was stirred at 30°C for 2 h, then aged at room temperature for 0.5 h. After that, the mixture was filtered and washed with water three times, and dried in an oven at 90°C for 13 h to obtain a catalyst sample. After tabletting, it was sieved with a 20-40 mesh sieve.
[0087] The bimetallic sulfate composite catalyst prepared above was used to catalyze the cracking of 1,1-difluoro-1-chloroethane (HCFC-142b) to prepare 1,1-difluoroethylene (VDF). The reaction conditions were as follows: the catalyst was loaded into a fixed bed reactor with a catalyst loading of 2 mL, a mixed gas of N2 and HCFC-142b was introduced, the N2 flow rate was 5 mL / min, the HCFC-142b flow rate was 5 mL / min, and the total space velocity of the mixed gas of N2 and HCFC-142b was 300 h / min. -1 , the reaction temperature was 400°C. Samples were taken and analyzed after 30 hours of reaction, and the evaluation results are shown in Table 6.
[0088] Table 6: Conversion rate of HCFC-142b and selectivity of VDF for catalysts with different Ni contents
[0089]
[0090] It can be seen from the experimental results of Examples 7 to 18 that when the sulfate of any one of the metals Y, Sr, Ca, and Ni is used as a co-catalyst and the reaction is continuously evaluated for 30 hours, the VDF selectivity of the catalytic reaction is basically maintained at more than 90%, and the catalytic conversion rate can reach more than 80%, achieving good technical results.
[0091] Embodiment 19
[0092] Dissolve 0.040 mol Ba(NO3)2 in 100 mL deionized water at 40°C, stir in a water bath for 30 min, then add dropwise 100 mL 0.400 mol / L (NH4)2SO4 aqueous solution, keep stirring at 40°C for 3 h, then age at room temperature for 1 h, filter and wash with water 3 times, then dry in an oven at 90°C for 12 h to obtain a catalyst sample, press into tablets and sieve with a 20-40 mesh sieve.
[0093] The bimetallic sulfate composite catalyst prepared above was used to catalyze the cracking of 1,1-difluoro-1-chloroethane (HCFC-142b) to prepare 1,1-difluoroethylene (VDF). The reaction conditions were as follows: the catalyst was loaded into a fixed bed reactor with a catalyst loading of 2 mL, a mixed gas of N2 and HCFC-142b was introduced, the N2 flow rate was 5 mL / min, the HCFC-142b flow rate was 5 mL / min, and the total space velocity of the mixed gas of N2 and HCFC-142b was 300 h / min. -1 , the reaction temperature was 425°C. Sampling analysis was performed after 30 hours of reaction, and the evaluation results are shown in Table 7.
[0094] Table 7
[0095]
[0096] It can be seen from the experimental results of Example 19 that when BaSO4 is directly used as a catalyst and the reaction is continuously evaluated for 30 hours, although the catalytic selectivity remains at a high level, the conversion rate is only 56.3%, and the catalytic effect is not ideal.
[0097] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.
Claims
1. Application of a bimetallic sulfate composite catalyst in the catalytic gas phase dehydrochlorination of fluorinated chloroalkanes to prepare fluorinated olefins, characterized in that The composite catalyst is a bimetallic sulfate composite catalyst with BaSO4 as a main catalyst and sulfate of any one metal among Pb, Ag, Y, Sr, Ca and Ni as a co-catalyst.
2. The use according to claim 1, characterized in that The composite catalyst is prepared by a coprecipitation method, comprising the following steps: 1) Dissolve the barium source and the co-catalyst precursor in deionized water, stir for 20-40 minutes, then drop the aqueous solution of the precipitant into the solution, stir and react for 2-4 hours to obtain a precipitated mixture; 2) The precipitated mixture obtained in step 1) is aged at room temperature, then filtered, washed with water, and dried to obtain a bimetallic sulfate composite catalyst.
3. The use according to claim 2, characterized in that The barium source in step 1) is one of barium nitrate, barium chloride or barium hydroxide.
4. The use according to claim 3, characterized in that The barium source in step 1) is barium nitrate.
5. The use according to claim 2, characterized in that In step 1), the catalyst precursor is one of the nitrates, chlorides or hydroxides of any one of the metals of Pb, Ag, Y, Sr, Ca and Ni.
6. The use according to claim 5, characterized in that In step 1), the catalyst precursor is a nitrate of any one of the metals Pb, Ag, Y, Sr, Ca and Ni.
7. The use according to claim 6, characterized in that In step 1), the promoter precursor is a nitrate of any one of the metals Y, Sr, Ca and Ni.
8. The use according to claim 2, characterized in that In step 1), the molar ratio of the metal element in the co-catalyst precursor to the barium element in the barium source is 0.01-2:
1.
9. The use according to claim 8, characterized in that In step 1), the molar ratio of the metal element in the co-catalyst precursor to the barium element in the barium source is 0.1-1:
1.
10. The use according to claim 2, characterized in that In step 1), the stirring reaction temperature is 10-70°C.
11. The use according to claim 10, characterized in that In step 1), the stirring reaction temperature is 30-50°C.
12. The use according to claim 2, characterized in that In step 1), the precipitant is one of ammonium sulfate, ammonium bisulfate or dilute sulfuric acid, and the molar ratio of the precipitant to the barium element in the barium source is 1-2:
1.
13. The use according to claim 12, characterized in that In step 1), the molar ratio of the precipitant to the barium element in the barium source is 1.1-1.5:
1.
14. The use according to claim 2, characterized in that In step 2), the aging time is 0.2~3h; the drying temperature is 60~140°C, and the drying time is 8~16h.
15. The use according to claim 14, characterized in that In step 2), the aging time is 0.5~1.5h; the drying temperature is 90~110°C, and the drying time is 11~13h.
16. The use according to claim 9, characterized in that The fluorine-containing chloroalkane is 1,1-difluoro-1-chloroethane, and the fluorine-containing olefin is vinylidene fluoride; The process of using the bimetallic sulfate composite catalyst in catalyzing the gas-phase dehydrochlorination of fluorinated chloroalkanes to prepare fluorinated olefins is as follows: the catalyst is loaded into a fixed bed reactor, a mixed gas of N2 and fluorinated chloroalkanes is introduced, the feed volume ratio of N2 and fluorinated chloroalkanes is 1:0.5-2, and the total space velocity of the mixed gas of N2 and fluorinated chloroalkanes is 250-300 h -1 The reaction temperature is 350~450℃, and the reaction produces vinylidene fluoride product.
Citation Information
Patent Citations
Nitrogen oxide storing catalyst
CN1262144A
Improvements in the production of fluorescent materials
GB562696A
Sulfide oxidizing catalyst and sulfide concentration measuring device using this catalyst
JP2000325790A